Prognostic effect of lncRNA BBOX1-AS1 in malignancies: a meta-analysis - Lin, Guangyao; Wang, Yongzhou; Deng, Li; Ye, Tao (Frontiers in Genetics, 2023)
Background: With the increasing numbers of new cancer cases and mortality rates, cancer has become a serious global health problem, but there are no ideal cancer biomarkers to diagnose effectively. Currently, mounting evidence demonstrates that lncRNAs play a fundamental role in cancer progression. BBOX1 anti-sense RNA 1 (BBOX1-AS1) is a recently clarified lncRNA and has been identified to be dysregulated in various carcinomas, and it contributes to poor survival in cancer patients.We thoroughly searched six databases for eligible papers published until 27 April 2023. The association of BBOX-AS1 expression levels with prognostic and clinicopathological parameters was assessed by odds ratios (ORs) and hazard ratios (HRs) with 95% CIs. Additionally, we further validated our results utilizing GEPIA online database.Results: Eight studies comprising 602 patients were included in this analysis. High BBOX-AS1 expression indicated poor overall survival (OS) (HR = 2.30, 95% Cl [1.99, 2.67], P < 0.00001) when compared with low BBOX-AS1 expression.Furthermore, increased BBOX-AS1 expression was positively correlated with lymph node metastasis (OR = 3.00, 95% CI [1.71 -5.28], P = 0.0001) and advanced tumor stage (OR = 3.74, 95% CI [2.63 -5.32], P < 0.00001) for cancer patients. Moreover, BBOX-AS1 was remarkably upregulated in 12 malignancies, and the elevated BBOX-AS1 expression predicted poor OS and worse disease-free survival (DFS) confirmed through the GEPIA online gene analysis tool.The findings highlight that BBOX-AS1 was significantly associated with detrimental OS, DFS, lymph node metastasis, and tumor stage; thus, it could be acted as a novel promising biomarker to predict the clinicopathological characteristics and prognosis for various cancers.